2020
DOI: 10.1177/1065912920933668
|View full text |Cite
|
Sign up to set email alerts
|

It Takes a Motive: Communal and Agentic Articulated Interest and Candidate Emergence

Abstract: More women ran for office in 2018 than any previous election year. This represents progress toward parity, but it remains unclear whether this surge in women’s political ambition signals an easing of the candidate emergence path, which has typically favored men. We leverage over ten thousand intake forms of prospective candidates provided by Run for Something, a candidate recruitment nonprofit founded in 2017, to examine patterns in candidate emergence based on articulated interest through the lens of “communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Scholars attribute women's lower average ambition to gendered socialization(Fox and Lawless 2004;Lawless and Fox 2005), perceived lower odds of success(Barber, Butler, and Preece 2016;Fulton et al 2006;Kanthak and Woon 2015; Maestas et al 2006, but cf. Deason, Greenlee, andLangner [2015] andKarpowitz, Monson, and Preece [2017] for exceptions), lack of mentorship(Kalla, Rosenbluth, and Teele 2018), beliefs that politics are less useful for them(Conroy and Green 2020;Shames 2017;Schneider et al 2016), or decisions to seek roles in the private sector(Sidorsky 2019). These dynamics may be different for women of color(Bejarano 2013;Brown 2014;Githens and Prestage 1977;Holman and Schneider 2018;Shah, Scott, and Juenke 2019;Smooth 2006).…”
mentioning
confidence: 99%
“…Scholars attribute women's lower average ambition to gendered socialization(Fox and Lawless 2004;Lawless and Fox 2005), perceived lower odds of success(Barber, Butler, and Preece 2016;Fulton et al 2006;Kanthak and Woon 2015; Maestas et al 2006, but cf. Deason, Greenlee, andLangner [2015] andKarpowitz, Monson, and Preece [2017] for exceptions), lack of mentorship(Kalla, Rosenbluth, and Teele 2018), beliefs that politics are less useful for them(Conroy and Green 2020;Shames 2017;Schneider et al 2016), or decisions to seek roles in the private sector(Sidorsky 2019). These dynamics may be different for women of color(Bejarano 2013;Brown 2014;Githens and Prestage 1977;Holman and Schneider 2018;Shah, Scott, and Juenke 2019;Smooth 2006).…”
mentioning
confidence: 99%
“…However, political candidates often present specific characteristics as compared to the general population (e.g., Caprara et al, 2003 ). In line with this view, Conroy and Green (2020) have stressed how female candidates might be more agentic than women with lower political ambition. It can thus be important to focus on how politicians present themselves in social media, analyzing also the phenomenon in different contexts that are characterized by variable levels of personal control and motivation over the transmitted contents.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, women who decide to run for political offices may be characterized by specific motivational and personality profiles. For instance, Conroy and Green (2020) showed that women candidates employ more agentic words compared to women noncandidates. In addition, they found that differences in agency and communion between candidates and non-candidates were greater compared to those between women and men, supporting the idea that female politicians who run for political offices are characterized by overall high levels of agency.…”
Section: Introductionmentioning
confidence: 99%
“…7) suggests that, controlling for some observables, political interest is not correlated with actual candidacy, perhaps due to structural barriers. On the other hand, Green & Conroy (2020) show that initial statements of interest from political aspirants predict eventual candidacy.…”
Section: Behavioral Measures Of Political Entry and The Political Entry Pipelinementioning
confidence: 96%